2004
DOI: 10.1023/b:mcbi.0000028761.61216.5e
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-dependence of contraction in streptozotocin-induced diabetic myocytes

Abstract: Cardiac contractile dysfunction is frequently reported in human patients and experimental animals with type-1 diabetes mellitus. The aim of this study was to investigate the voltage-dependence of contraction in ventricular myocytes from the streptozotocin (STZ)-induced diabetic rat. STZ-induced diabetes was characterised by hyperglycaemia and hypoinsulinaemia. Other characteristics included reduced body and heart weight and raised blood osmolarity. Isolated ventricular myocytes were patched in whole cell, volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 49 publications
4
28
0
Order By: Relevance
“…Many previous studies have also reported a null effect of diabetes on peak active stress (i.e., when the muscle is held at L o ) at stimulus frequencies ≤ 1 Hz in isolated papillary muscles [2,3,28,30,34-37] and in isolated single myocytes [46,47,49]. But, there are several studies showing lower contractility of diabetic myocytes at stimulus frequencies ≤ 1 Hz [31,38,57] as well as at 2 Hz [29].…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have also reported a null effect of diabetes on peak active stress (i.e., when the muscle is held at L o ) at stimulus frequencies ≤ 1 Hz in isolated papillary muscles [2,3,28,30,34-37] and in isolated single myocytes [46,47,49]. But, there are several studies showing lower contractility of diabetic myocytes at stimulus frequencies ≤ 1 Hz [31,38,57] as well as at 2 Hz [29].…”
Section: Discussionmentioning
confidence: 99%
“…Net influx of Ca 2+ was reported to be significantly reduced in chronic 4-8 weeks diabetic rat myocardium [29]. Although some studies have shown normal function of LTCC [18,20,30], others have established a reduction in LTCC protein expression with the consequent decrease in I Ca density in T1D myocytes compared with control myocytes [17,28,31,32]. Besides LTCC expression, the biophysical properties of the LTCCs are altered.…”
Section: Ca 2+ Entry/influxmentioning
confidence: 99%
“…Thus, it seems that overexpressed NCX can compensate to maintain adequate contractile function by increasing Ca 2+ entry [23]. Moreover, it has also been observed a prolonged action potential duration (APD) in experimental animals with T1D supporting the increased activity of NCX in the reverse mode [31]. Ca 2+ influx is also favored in T1D by APD prolongation, resulting from decrease in transient outward potassium current (I to ) [70].…”
Section: Ca 2+ Extrusion/effluxmentioning
confidence: 99%
“…After dot blot analysis confirming the delivery of administered R7W-MP to the heart, the effect of R7W-MP on cardiac function was monitored (Figure VA in the online-only Data Supplement). In vivo echocardiographic analyses revealed no differences between groups (Table I in To investigate the potential therapeutic application of R7W-MP, we assessed its effect in a mouse model of streptozotocin-induced diabetes mellitus in which alteration of cardiac contractility and reduced LTCC density are secondary consequences of the disease 10,[35][36][37][38][39] (Figure 6A and 6B and Tables II and III in On the basis of these outcomes, we explored the potential translatability of our results and retrospectively analyzed left ventricular biopsies from diabetic and nondiabetic cardiomyopathy patients with aortic stenosis undergoing aortic valve replacement. Interestingly, we found a direct linear correlation between the total amount of Ca v α1.2 and the Akt-dependent phosphorylation status of Ca v β2 (Figure 7).…”
Section: R7w-mp Restores Cardiac Function In Vivo Through Modulation mentioning
confidence: 99%